The Effectiveness of Article 21 Corporate Income Tax Revenues Using Progressive Calculation Based on the Average Effective Rate (AER) in 2023–2024 - Muhammad Rufi; Mustofa Ahmad Yunus; Moh. Yudi Mahadianto; Asep Basuki (Riviera Publishing, 2025)
Taxes serve as the primary source of state revenue and play a strategic role in financing national development and public services. This study aims to evaluate the effectiveness of income tax (PPh) Article 21 collection by corporate taxpayers, particularly following the implementation of the Average Effective Tax Rate (TER) policy in 2024. The policy was introduced to simplify the previously applied progressive tax structure, with the expectation of improving administrative efficiency and taxpayer compliance. Employing a descriptive qualitative approach, data were collected through interviews, observations, and documentation at the Cirebon Satu Primary Tax Office (KPP Pratama Cirebon Satu). The results reveal that the introduction of TER has not yet led to an increase in tax revenue. On the contrary, there was a significant decline of over 33% in PPh Article 21 receipts during the first year of implementation. This decrease is attributed to limited understanding among corporate taxpayers regarding the new TER scheme, insufficient technical outreach, and systemic difficulties in adjusting payroll calculations.